1976
DOI: 10.1042/bj1550193
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal amino acid sequence of wheat proteins that lack phenylalanine and histidine residues

Abstract: The 24 residues of the N-terminal CNBr peptide from a wheat albumin, that lacks phenylalanine and histidine, have been sequenced. Three of the assignments were made partly by analogy with two other proteins, as evidence is presented that all three proteins are probably identical in this region. Extra evidence for the sequences of the alpha-chymotryptic peptides derived from the N-terminal CNBr peptides of the three proteins, and also for their assembly, has been deposited as Supplementary Publication SUP 50063… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The recovery of the N-terminal residue (serine) was close to 60 %; such a yield, which is usual for single-chain proteins (Niall, 1973), suggests that this residue was derived from both subunits of inhibitor 0.19. In agreement with the previous reports by Redman (1975Redman ( , 1976, we found that serine is also the N-terminal residue of inhibitor 0.28. We were unable to identify the amino acid phenylthiohydantoin released at the second cycle of the automated Edman procedure with inhibitor 0.19; this product did not give any characteristic peak by g.l.c.…”
Section: Chemical Studiessupporting
confidence: 93%
See 3 more Smart Citations
“…The recovery of the N-terminal residue (serine) was close to 60 %; such a yield, which is usual for single-chain proteins (Niall, 1973), suggests that this residue was derived from both subunits of inhibitor 0.19. In agreement with the previous reports by Redman (1975Redman ( , 1976, we found that serine is also the N-terminal residue of inhibitor 0.28. We were unable to identify the amino acid phenylthiohydantoin released at the second cycle of the automated Edman procedure with inhibitor 0.19; this product did not give any characteristic peak by g.l.c.…”
Section: Chemical Studiessupporting
confidence: 93%
“…These two proteins with identical molecular weight not only have similar inhibitory behaviour towards a-amylases from Vol. 173 different origins (Silano et al, 1973) and have homologous amino acid sequences of large peptide fragments (Redman, 1975(Redman, , 1976, but are also characterized by an identical content of disulphide bridges and closely related conformations as monitored by c.d. spectra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 3 was used in this study in its nonphosphorylated form only. The basic sequence in 3, Tyr-Lys-Val, occurs naturally in wheat albumin (Redman, 1976), and the preparation and biological evaluation of its N-phosphorylated form will be reported later. Its characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%